PENTINGNYA LAPORAN NILAI TAMBAH DALAM PELAPORAN KEUANGAN (FINANCIAL VALUE ADDED/ FVA) SEBAGAI PENGUKUR KINERJA DAN PENCIPTAAN NILAI PERUSAHAAN (Fokus Ekonomi, 2008)
One of financial performance measurement concepts has been analyzed using FVA. While, company’s value added concept has not been analyzed using Financial Value Added (FVA). FVA is used to measure financial performance in a company and it is rarely used compares to EVA. The paper will explain in details about how to measure performance and value added of the company based on FVA and it is interrelated with decisions of financial management. However, this paper will explain the strengths and weaknesses of the measurement using financial ratio and EVA. Key words: Financial Ratio, Economic Value Added, Financial Value Added.